Assessment of COVID-19 among healthcare workers in Non-COVID pediatrics departments, Tehran, Iran: A cross-sectional study - Gholami, Narges; Farnaghi, Fariba; Pourmoshtagh, Hassan; Radfar, Mitra; Halimi Asl, Ali Asghar; Mehregan, Fatemeh Fereshteh; Gachkar, Latif (Researcher Bulletin of Medical Sciences, 2022)
Objective: The severe acute respiratory syndrome coronavirus 2(SARS COV 2) is an important health problem, which is widespread around the world. This study describes the characteristics of COVID-19 infections in healthcare workers (HCWs), related factors and deaths in Non- COVID pediatrics departments from the early phases of COVID-19 pandemic; February 20th, 2020toJanuary19th, 2021 in Tehran-Iran. Materials and Methods: It is a multi-center cross-sectional descriptive study. The standardized questionnaire was designed according Demographics information, Coronavirus disease (COVID-19) history in HCW and Using and access to Personal Protective Equipment (PPE). All data analysis was performed by SPSS software version 21. Results: Of the 82 HCW, 67 (81.7%) was female. The median age was 37.6 ±10.3 years old (rang 24 to 65). 44 (53.6%) were nurses, 14 (17 %) pediatrics residents,13 (15.9%) pediatrics faculty members,8(9.8%) environmental services staff and 3(3.7%) secretaries. Twelve out of our cases (14.6%) have underlying medical diseases. Thirty-six (42.7%) confirmed COVID19. In COVID-19 positive group 28(80%) were female. Among whom 51.4% were identified nurses, 17% faculty member and14.3% pediatrics residents. Secretaries and environmental services staff are more vulnerable job category in this study. Eighty-six percent of them follow protective health protocol and use PPE. COVID-19 cases were infected more on July 2020(25.7%), November 2020 (17.1%) and August 2020(14.2%). Conclusion: Approximately one half of HCWs in non-Covid-19 pediatrics department infected with corona virus 2 (SARS_COV_2) and most of them thought they were infected in workplace